Identidad fragmentada... Identidad performativa: del estilo a las culturas juveniles (2003)
Urban, juvenile, cultures, are configured as spaces of identity and socialization of youths for youths, and are strengthened with the weakening of the traditional integration mechanisms (school, family, works religion) and the disrepute of the political institutions, in this context, urban cultural studies acquire relevance, where young people emerge as individuals and as productive groups of Culture because of their ways of understanding and taking on the world.The juvenile Cultures are confronting the structuring identity, thus we recognize in them the emergence of instable, mobile, current, rootless identities... which confront the traditional notion of identity: fixed, unique, and homogeneous. The renewed juvenile identities are denominated fragmented identities... pre-formative identities, for the identities developed in juvenile cultures are adapted, disfigured, or reconstructed by the young people: they invent their own identity and even more so, they are unfaithful, that is, they resist to remaining any polished, defined, determined, or structured identity.The collective relationship, juvenile culture-esthetics-identity, opens up a renewed perspective of researching which we are carrying out to the University of Medellin and it pretends to show the core role Which music fulfills as a juvenile identity force which, furthermore, enhances the possibilities of creation and cultural production of the youths for the youths.